Perancangan Arsitektur Sistem Informasi Pondok Pesantren Dengan The Open Group Architecture Framework (Togaf) - Yaqin, M. Ainul; Sa’adah, Alfionita; Puspithasari, Nanda Nafisah; Rahma, Lutfia Miftahur (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2020)
Islamic boarding school is a place of learning in which there are very many facilities and services. Good mastery of language, creativity, religion, leadership and all kinds of knowledge must already exist in the boarding school. The current condition of many Islamic boarding schools does not yet have a specific and integrated information system architecture in Islamic boarding schools in accordance with the needs and objectives of Islamic boarding schools, the cause is because Islamic boarding schools have not yet focused on the process of developing their information systems. Therefore we need an information system in Islamic boarding school. In this study the author raised the information system design of Islamic boarding school by using TOGAF (The Open Group Architecture Framework) with the Architecture Development Method (ADM) method. The output that can be achieved from the design of Islamic Boarding School Information System is to produce a model and basic framework (blue print) in developing integrated boarding school information systems to support the needs of Islamic Boarding Schools.